2016
DOI: 10.1186/s13660-016-0974-7
|View full text |Cite
|
Sign up to set email alerts
|

Berwald-type inequalities for Sugeno integral with respect to ( α , m , r ) g ${ ( {\alpha,m,r} )_{g}}$ -concave functions

Abstract: In this paper, we introduce the concept of an (α, m, r) g -concave function as a generalization of a concave function. Then we establish Berwald-type inequalities for the Sugeno integral based on this kind of functions. Our work generalizes the previous results in the literature. Finally, we give some conclusions and problems for further investigations.MSC: 03E72; 28B15; 28E10; 26D10

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 39 publications
1
33
0
Order By: Relevance
“…After the MBC was modified further with TC-CS, in the resulting TMBC spectrum, the broad band centered on around 3450 cm 21 was strengthened; this was associated with the AOH stretching vibrations of the hydroxyl groups in the pyranose rings or the adsorbed water molecules. 27,30 The appearance of ACHA asymmetric and symmetric stretching vibrations around 2900 cm 21 , 31 the two new peaks at about 1545 and 1250 cm 21 , were attributed to the C@S bonds of the thiourea group stretching vibrations; 30,32 this confirmed the occurrence of TC-CS in the TMBC sample structure.…”
Section: Sample Characterizationmentioning
confidence: 91%
See 1 more Smart Citation
“…After the MBC was modified further with TC-CS, in the resulting TMBC spectrum, the broad band centered on around 3450 cm 21 was strengthened; this was associated with the AOH stretching vibrations of the hydroxyl groups in the pyranose rings or the adsorbed water molecules. 27,30 The appearance of ACHA asymmetric and symmetric stretching vibrations around 2900 cm 21 , 31 the two new peaks at about 1545 and 1250 cm 21 , were attributed to the C@S bonds of the thiourea group stretching vibrations; 30,32 this confirmed the occurrence of TC-CS in the TMBC sample structure.…”
Section: Sample Characterizationmentioning
confidence: 91%
“…The adsorption capacities of Cd(II) by the three various BC adsorbents sharply increased with the initial solution pH increasing from 3.01 to 5.98, whereas at pH above 5.98, the adsorption amounts gradually became steady. A lowered solution pH was conducive to the adsorbent surface protonation and resulted in the H 1 competition with positive Cd(II) ions, although the increasing pH led to the positively charged adsorbent surface gradually changing to negative because of the deprotonation effect; this resulted in increased electrostatic inductive interactions between the negatively charged surface and positive ions 30 and an increase in the Cd(II) adsorption amounts. We found that the zero point of charge (pH zpc ; DpH 5 0) of TMBC was around 7, whereas the pH zpc values of BC and MBC were all above 8 [ Figure 3(b)].…”
Section: Effect Of the Initial Solution Phmentioning
confidence: 99%
“…Sun and co-workers also investigated the properties of liquid-crystalline polymers. [61][62][63] They synthesized terpolymers, P6 , by the melt polycondensation of Macromol. Rapid Commun.…”
Section: Direct Polymerization Methodsmentioning
confidence: 99%
“…Properties of the terpolymers synthesized from p -hydroxybenzoic acid, polyethylene terephtalate, and a third monomer [61][62][63]. …”
mentioning
confidence: 99%
“…[59] The sup- port may decrease the electron density of the porphyrin ring and thus increase its oxidizing ability with enhanced electron-withdrawing properties. [60,61]…”
Section: Catalytic Activitymentioning
confidence: 99%